First, remove the parentheses
-7+2x+7=-7
Cancel the equal terms.
2x+7=0
Subtract 7
2x= -7
Divide both sides by 2
Final answer is:
X= -3.5
Answer:
A
Step-by-step explanation:
Sorry if I am wrong
it is kinda confusing
Answer:
y= -1
Explanation:
Isolate the variable by dividing each side by factors that don't contain the variable.
Answer:
y = 2x
y = 3x - 3
Step-by-step explanation:
Hi,
<u>y = 2x</u>
<u>6 = 2(3)</u>
<u>6 = 6</u>
<u>That's a solution</u>
<u>y = 3x - 3</u>
<u>6 = 3(3) - 3</u>
<u>6 = 9 - 3</u>
<u>6 = 6</u>
<u>That's a solution</u>
Hope this helps :)